(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
The article examines the linguocultural features of literary translation within the framework of modern translation studies and linguoculturology. Literary translation is viewed as a form of intercultural and interliterary communication that ensures the transmission of cultural meanings and the national worldview of the source text. The study substantiates the need to integrate literary translation theory with intercultural communication studies and emphasizes the mediating role of translation in overcoming cultural alienation and fostering dialogue between cultures.